Creation of e-pathfinders for the graduate and undergraduate subjects of the University of the Philippines School of Library and Information Studies - Santos, Jonathan F.; Dorado, Dan Anthony D.; Santos, Mark Anthony A. (Quezon City School of Library and Information Studies, University of the Philippines, Diliman, 2019)
Much effort is needed to sustain the development of a culture of research in the field of library and information science (LIS). The creation of additional finding tools such as pathfinders or research guides will greatly help library users in their academic and research works. Electronic pathfinders provide a unique opportunity for librarians since they function as guides to resources available in a particular library while capitalizing on the various capabilities of the Internet in terms of access. With various options on the implementation of e-pathfinders currently available, providing this service is something librarians should highly consider.

This project aims to implement and create e-pathfinders for the University of the Philippines (UP) School of Library and Information Studies (SLIS) Library. A free and open-source, database-driven software called SubjectsPlus was used to provide a platform for the creation of subject guides based on the courses offered by UP SLIS. Online databases related to LIS and other research tools were obtained from the University Library website while the most recent and related print resources, which include books, journals, reference materials, and theses, were retrieved from iLib, the online catalog of UP. These were encoded, arranged and redesigned, with the resulting system being branded as LIS Finder.

It is hoped that this project will help UP SLIS Library users in their studies and researches, make library resources more accessible, and in the long term, serve as a forward step in the advancement of LIS research culture in the Philippines.
Special Problem
Keywords: University of the Philippines. -- School of Library and Information Studies; Electronic information resources; Reference services (Libraries).; Information resources